2018
DOI: 10.3906/tar-1802-3
|View full text |Cite
|
Sign up to set email alerts
|

Cereal source and microbial consortia of the starter culture influence the chemical composition and physicochemical characteristics of boza

Abstract: Boza is a popular cereal-based traditional beverage particularly consumed during winter months in Balkan countries and Turkic societies. The present study aims to investigate the influence of different cereal sources and starter cultures used in the commercial production of boza on its chemical and microbiota compositions and physicochemical characteristics. Detailed experimentation has revealed that chemical compositions, i.e. carbohydrates (beta-glucans, starches), organic acids, vitamins, dietary fibers, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…(L. plantarum, L. paracasei, L. brevis, L. delbrueckii subsp. delbrueckii) were identified as the common members of the microbial community in the boza samples (Borcaklı, Öztürk, & Yeşilada, 2018). In our study, initial cultural examination revealed 29 presumptive LAB strains (1 E. faecium, 11 L. casei, 1 L. fermentum, 6 L. pentosus, 3 L. lactis and 7 P. pentosaceus) from the fermented sourdoughs.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…(L. plantarum, L. paracasei, L. brevis, L. delbrueckii subsp. delbrueckii) were identified as the common members of the microbial community in the boza samples (Borcaklı, Öztürk, & Yeşilada, 2018). In our study, initial cultural examination revealed 29 presumptive LAB strains (1 E. faecium, 11 L. casei, 1 L. fermentum, 6 L. pentosus, 3 L. lactis and 7 P. pentosaceus) from the fermented sourdoughs.…”
Section: Resultsmentioning
confidence: 59%
“…On the other hand, L. plantarum (24%), L. acidophilus (23) and L. fermentum (19%) were dominant in the Bulgarian boza, whereas L. plantarum was the major species isolated from Turkish boza samples (Gotcheva et al, 2001;Kivanc et al, 2011;Lokumcu Altay et al, 2013). A recent study in Turkey by Borcaklı et al (2018) showed that various LAB involving Lactococcus lactis, leuconostocs (L. pseudomesenteroides, Lc. lactis, Lc.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation